Immunoregulatory properties of cell-free DNA in plasma of celiac disease patients - A pilot study - Brynychova, Iva; Zinkova, Alzbeta; Hoffmanova, Iva; Korabecna, Marie; Dankova, Pavlina (Autoimmunity, 2019)
The elevated plasma cell-free DNA (cfDNA) concentrations were repeatedly reported in association with the process of inflammation. The qualitative and quantitative characteristics of plasma cfDNA in active (newly diagnosed) celiac disease patients (CD) have not yet been studied despite the fact that cfDNA of healthy individuals is able to regulate immune response. We determined the total cfDNA concentration and relative content of telomeric sequences in plasma cfDNA in CD (n = 10) and healthy age- and sex-matched controls (HC, n = 10) by quantitative PCR. To obtain the evidence that the observed biological effects are caused solely by cfDNA molecules, we applied the treatment of paired plasma samples with DNase. Using paired samples of plasma (non-treated/native and treated by DNase), we analyzed the contribution of cfDNA to the activation of TLR9 and TNF-α mRNA expression in THP1 monocytic cell line. There were no significant differences in the quantities of plasma cfDNA and relative contents of telomeric sequences in their pools. When we compared the levels of TNF-α mRNA expression in THP1 cells achieved after stimulation with native CD and HC plasma samples, we found significantly (p = .031) higher expression after stimulation with CD samples. We documented also the ability of cfDNA contained in CD plasma samples to stimulate the production of TLR9 mRNA. The TLR9 mRNA expression levels were significantly (p = .014) lowered after cfDNA removal from CD plasma samples. The design of our experiments allowed us to study the effects of cfDNA without its isolation from plasma. cfDNA contained in CD plasma samples differs significantly in its immunoregulatory capacity from cfDNA in HC plasma. The differences are caused neither by different concentrations of cfDNA in plasma samples nor by different relative abundance of telomeric sequences. Further studies are needed to elucidate the role of plasma cfDNA in celiac disease pathogenesis.
Keywords: toll-like receptor 9; Humans; regulace genové exprese; telomeric sequences; Female; dospělí; lidé; TNF-α; THP-1 buňky; pilotní projekty; Pilot Projects; TNF-alfa; Adult; imunologické faktory; celiakie; ženské pohlaví; Gene Expression Regulation; Male; Toll-Like Receptor 9; Celiac disease; Cell-Free Nucleic Acids; cell-free DNA; volné cirkulující nukleové kyseliny; Celiac Disease; Immunologic Factors; Real-Time Polymerase Chain Reaction; Tumor Necrosis Factor-alpha; mužské pohlaví; THP-1 Cells; kvantitativní polymerázová řetězová reakce